Inovasi Pengolahan Pangan Berkelanjutan untuk Meningkatkan Kesehatan Masyarakat: Kajian Literatur (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2025)
This study aims to analyze various sustainable food processing innovations that contribute to improving public health in Indonesia. The research was conducted through a literature review of 13 scientific articles published between 2015 and 2025 that discussed aspects of nutritional innovation, environmentally friendly processing technology, social empowerment, and food waste management. The analysis results indicate that the use of local food ingredients such as moringa leaves, snakehead fish, and soybeans plays a significant role in improving nutritional literacy, preventing stunting, and strengthening family food security. Meanwhile, the application of appropriate technologies such as oil draining machines, energy-efficient dryers, and waste processing into organic fertilizer contributes to production efficiency and reduced environmental impact. Furthermore, social innovation through the empowerment of MSMEs and women's groups can strengthen the local economy and foster environmental awareness. Thus, the synergy between nutritional, technological, and social innovations forms the basis for developing a healthy and sustainable food system to support the achievement of SDGs 2 and 3 in Indonesia.